Application of the Consolidated Framework for Implementation Research Model to Design and Implement an Optimization Methodology within an Ambulatory Setting - Touson, Jonathan C.; Azad, Namita; Beirne, Jennifer; Depue, Corinne R.; Crimmins, Timothy J.; Overdevest, Jonathan; Long, Rosalie (Applied Clinical Informatics, 2022)
Background Following the implementation of a new electronic health record (EHR) system at Columbia University Irving Medical Center (CUIMC), the demands of the novel coronavirus disease 2019 (COVID-19) pandemic forced an abrupt reallocation of resources away from EHR adoption. To assist staff in focusing on techniques for improving EHR utilization, an optimization methodology was designed referencing the Consolidated Framework for Implementation Research (CFIR) approach.Methods The study was performed using a methodology that comprised of two primary components as follows: (1) analysis of qualitative and quantitative data and (2) participation of frontline staff in project work groups. Working groups mapped out the current state of the identified workflows, designed and implemented interventions, monitored the effectiveness of each intervention, and scaled the proposed changes.Results As a result of the optimization methodology, clinical and operational workflows improved in the pilot department. Operationally, the pilot department increased enrollment of patients in the virtual patient portal by 20%, increased schedule utilization by 25%, and reduced average check-in time by 19%. Clinically, the pilot department had a statistically significant increase in dictation and NoteWriter tool note composition from their baseline month to their observed month. Compared with the control department, the pilot department had a statistically significant increase in SmartTool and dictation note composition. The control department showed smaller increases, and in some cases a decline in performance, in these areas of operational and clinical workflows.Conclusion The CFIR framework helped design an optimization methodology by applying a set of constructs to support effective organizational optimization, accounting for inner and outer settings. Through this methodology, the inner setting was supported in leading the identification and execution of interventions targeted to impact the outer setting. The phase-1 data at CUIMC suggest this strategy is effective in identifying opportunities, implementing interventions and creating a scalable process for continued organizational optimization.
Keywords: electronic health records; optimization; ambulatory; COVID-19; consolidated framework for implementation research